2023
DOI: 10.1038/s41584-023-00944-2
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the secosteroid vitamin D in autoimmune rheumatic diseases and COVID-19

Abstract: Evidence supporting the extra-skeletal role of vitamin D in modulating immune responses is centred on the effects of its final metabolite, 1,25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 , also known as calcitriol), which is regarded as a true steroid hormone. 1,25(OH) 2 D 3 , the active form of vitamin D, can modulate the innate immune system in response to invading pathogens, downregulate inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 229 publications
1
19
0
1
Order By: Relevance
“…Moreover, in two different Iranian and Saudi Arabia cohorts (92 and 102 RA patients, respectively), hypovitaminosis D was significantly correlated with RA disease activity scores (DAS), like DAS28-CRP [11] or DAS28-ESR [12], as reported in previous studies [1].…”
supporting
confidence: 76%
“…Moreover, in two different Iranian and Saudi Arabia cohorts (92 and 102 RA patients, respectively), hypovitaminosis D was significantly correlated with RA disease activity scores (DAS), like DAS28-CRP [11] or DAS28-ESR [12], as reported in previous studies [1].…”
supporting
confidence: 76%
“…Vitamin D, as a secosteroid and a strong immunosuppressant, plays important roles in the autoimmune diseases. 43 Several studies have shown that VitD3 and its analogues inhibit the maturation of mDCs and maintained its immature phenotype, which can ameliorate autoimmune inflammation and induce immune tolerance. 18,44,45…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D 3 is a fat-soluble steroid hormone with pleiotropic biologic effects [ 1 ]. It is derived from both food and from the physiological photoconversion of cutaneous 7-dehydrocholesterol into pre-vitamin D 3 and then into cholecalciferol, following exposure to UV-B solar rays.…”
Section: Introductionmentioning
confidence: 99%
“…Schematically, when hydroxylation in position 1 occurs in the kidney, calcitriol exerts endocrine rapid non-genomic effects on target cells (gut epithelial cells, osteoblasts, osteoclasts, parathyroid cells, tubular renal cells), regulating calcium-phosphorus homeostasis (shown in Fig. 1 ) [ 1 ]. On the other hand, when hydroxylation in position 1 occurs in immune cells, calcitriol exerts paracrine/autocrine slower genomic effects on immune cells themselves, downregulating autoimmune/inflammatory processes (shown in Fig.…”
Section: Introductionmentioning
confidence: 99%